Pengaruh Customer Relationship Management Terhadap Loyalitas Pelanggan TV Kabel di Kecamatan Tembalang Melalui Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada PT. MNC Sky Vision-Indovision Semarang) - Zahro, Nurul Ulfa; Prabawani, Bulan (Jurnal Ilmu Administrasi Bisnis, 2018)
By providing a good CRM, Indovision has been doing an effort to keep customers’ satisfaction and make the consumers become loyal. The purpose of this study is to determine the influence of CRM as X variable towards loyalty as Y variable through variable Z that is satisfaction. The type of this research is an explanatory research. This research uses non-probability sampling technique to 100 samples who are the consumers in Tembalang Sub-district. This research uses purposive sampling and accidental sampling. The data analysis technique used is cross tabulation test, correlation test, determination test, simple linear regression test, multiple linear regression test, t test, F test, sobel test with the help of IBM SPSS (Statistical Product and Service Solution) program 21.0 version. The results show that CRM gives positive and significant influence towards satisfaction with regression of coefficient value 0.349 and t-value 8,187 and correlation of coefficient value 0.616 and coefficient of determination 40.3%. Satisfaction has a positive and significant influence on loyalty with regression of coefficient value 0.591 and t-value 7.210 and correlation of coefficient value 0.586 and determination of coefficient value 34.1%. CRM has a positive and significant influence on the loyalty variable with regression of coefficient value 0.325 and t-value 7.227 and correlation of coefficient value 0.588 and determination of coefficient value 33.7%. CRM and Satisfaction have a positive and significant influence on the loyalty variable with F-value 35.687 and correlation of coefficient value 0.648 and determination of coefficient value 41.7%. Through the results of the sobel test, it shows that there is an influence between CRM on loyalty through satisfaction with t-value 3.188 and p-value 0.00311. The conclusion of this study is CRM affects Indovision customers’ loyalty through customers’ satisfaction. A suggestion that can be given to Indovision is Indovision should improve their services, especially customer complaints process, pay attention to criticism and suggestions given by customers and keep maintaining the CRM and the quality.